Comparison of immunity against canine distemper, adenovirus and parvovirus after vaccination with two multivalent canine vaccines - Rafes D. S. Cunha; Camilo L. daSilva Junior; Camilla A. Costa; Hulliana M. deAguiar; Danilo G. Junqueira Júnior (Veterinary Medicine and Science, 2020)
Abstract Background Viral diseases are a major cause of morbidity and mortality in puppies. There is a belief among veterinary practitioners and even educational institutions that the vaccines made in Brazil against canine distemper virus (CDV), canine parvovirus (CPV) and canine adenovirus (CAV) are ineffective or only partially effective. Objectives This study aimed at comparing the immunity of two multivalent vaccines in adult dogs in the city of Uberlândia, Minas Gerais state, Brazil. Methods The study was carried out at the Animal Protection Association and a total of 60 adult mongrel dogs were selected and divided into two groups. Group A was immunized with two doses of Elevencell® vaccine and Group B received two doses of imported vaccine from the United States; each group was made up of 14 females and 14 males. Results In group A, the Elevencell vaccine generated a protective antibody titre against CDV in 26 out of 28 subjects (92.85%), CPV in 24 out of 28 subjects (85.71%) and CAV in 26 out of 28 subjects (92.85%). In group B, the imported US vaccine generated a protective antibody titre against CDV in 22 out of 28 subjects (78.57), CPV in 21 out of 28 subjects (75%) and CAV in 25 out of 28 subjects (89.28%). There was no statistical difference between titres generated between vaccine types for any of the three diseases tested. Conclusion Elevencell vaccine titres were not inferior to the imported US vaccine in conferring protective titres against CDV, CPV and CAH, which confirms the efficacy of this product.